Olfactory Training for Postviral Olfactory Dysfunction: Systematic Review and Meta-analysis. (February 2021) - Kattar, Nrusheel; Do, Triet M.; Unis, Graham D.; Migneron, Matthew R.; Thomas, Andrew J.; McCoul, Edward D.
Objective: Olfactory dysfunction is a common problem that is most frequently attributed to upper respiratory infection. Postviral olfactory dysfunction (PVOD) can be prolonged and clinically challenging to treat. Olfactory training (OT) has demonstrated potential benefit for patients with nonspecific olfactory dysfunction. We sought to evaluate the efficacy of OT specifically for PVOD by pooled analysis of the existing evidence. Data Sources: PubMed, Embase, and Web of Science. Review Methods: Following PRISMA guidelines, PubMed, Embase, and Web of Science databases were queried and abstracts screened independently by 2 investigators. We included studies evaluating the efficacy of OT for PVOD and excluded studies evaluating pharmacologic interventions or olfactory loss from other causes. Results: Of the initial 1981 abstracts reviewed, 16 full-text articles were included. Sniffin' Sticks olfactory testing results were reported in 15 (93%) studies as threshold (T), discrimination (D), and identification (I) subscores and TDI total scores. All studies reported clinically significant results after OT, defined as a score improvement of TDI >5.5. Four studies were included in the meta-analysis, in which pooled estimates revealed that patients with PVOD who received OT had a 2.77 (95% confidence interval, 1.67-4.58) higher odds of achieving a clinically important difference in TDI scores compared to controls. Conclusion: Meta-analysis of existing data demonstrates clinically significant improvements in PVOD associated with OT. Variability exists among OT protocols and may benefit from further optimization. Existing data supports the use of OT for the treatment of existing and newly emerging cases of PVOD.